Faking Orgasm: Relationship to Orgasmic Problems and Relationship Type in Heterosexual Women. Issue 5 (20th August 2021) - Hevesi, Krisztina; Horvath, Zsolt; Sal, Dorottya; Miklos, Eszter; Rowland, David L.
Abstract: Introduction: Although faking orgasm among women appears quite common, the roles of orgasmic problems and relationship type in partnered sex and masturbation have not been fully explored. Aim: We assessed the relationship between orgasmic problems (separately in partnered sex and masturbation) and faking orgasm across various types of relationships while also considering the role of demographic and sexual function related covariates. Methods: In this study of 1, 168 Hungarian women, we assessed orgasmic problems, sexual functioning, and the prevalence and frequency of faking orgasm in 3 relationship types: romantic relationships, one-night stands, and continuing sexual relationships of more than one night. Main Outcome Measure: Differences in faking orgasm across 3 types of relationships; the association between faking orgasm in 1 type of relationship with faking orgasm in other types of relationships; and the relationship of "orgasmic problems" in partnered sex and masturbation to the presence and frequency of faking orgasm in various relationship types. Results: A subset of women who faked orgasm in 1 relationship type were more likely to fake orgasm in other relationship types. Orgasmic problems predicted the occurrence and frequency of faking orgasm in all 3 relationship types, though to different degrees. Other factors, including orgasmic difficulty during masturbation, the frequencies of masturbation and partnered sex, and the self-rated importance of sex were also related to the frequency of faking orgasm. Conclusion: Our findings suggest that faking orgasm has both dispositional and situational elements. "Orgasmic problems" in partnered sex was a consistent and robust predictor of the occurrence and frequency of faking orgasm in different relationship types.